Machine learning - Mitchell, Tom M. (Tom Michael), 1951- (New York : McGraw-Hill, 1997)
Introduction; Concept learning and the general-to-specific ordering; Decision tree learning; Artificial neural networks; Evaluating hypotheses; Bayesian learning; Computational learning theory; Instance-based learning; Genetic algorithms; Learning sets of rules; Analytical learning; Combining inductive and analytical learning; Reinforcement learning.
Includes bibliographical references and index.
Keywords: Computers; Machine; Machine learning; Computer algorithms